(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The Foreign Institutional Investors (FIIs) have materialized as important players in the Indian stock market and their increasing contribution adds as a significant feature of the improvement of stock markets in India. To make possible foreign capital flows, developing countries have been advised to make stronger their stock markets. As a result, the Indian Stock Markets have achieved new heights and became more volatile making the researches work in this measurement of establishing the link among FIIs and Stock Market volatility. Hence, it’s an motivating topic to ascertain the role of FIIs in Indian Capital Markets. This paper makes an attempt to grow an understanding of the dynamics of the trading performance of FIIs and effect on the Indian equity market. The study is conducted using daily data on BSE Sensex and FII activity over a period of 10 years spanning from 01st Jan 2001 to 31st Dec 2011. It provides the evidence of important positive correlation among FII activity and effects on Indian Capital Market. The analysis also finds that the movements in the Indian Capital Market are fairly explained by the FII net inflows.